The Declining Allure of Being “American” and the Proliferation of Corporate Tax Inversions: A Critical Analysis of Regulatory Efforts to Curtail the Inversion Trend - John C. Hamlett (Washington University Law Review, 2016)
In the realm of tax policy, within which there is rarely broad-based consensus, there are few topics as polarizing as corporate tax inversions. An inversion is a paper transaction in which a US corporation reincorporates abroad to realize strategic tax benefits, without actually transplanting its operations overseas. These transactions necessarily reduce the US corporate income tax base, because although an inverted corporation is still taxed the same amount on income earned within the United States, it will no longer have to remit tax payments to the US Department of the Treasury (“Treasury”) for income earned abroad. This reduction in the tax base is especially troubling given that the national debt exceeds $19 trillion, the US credit rating is experiencing unprecedented volatility, and the annual US government deficit ranges from hundreds of billions to more than a trillion dollars per year. Given the current state of the domestic economy, the notion of successful US corporations nominally moving their headquarters abroad to alleviate their tax burden is unpalatable for many. Others do not fault inverters for acting in the interests of their shareholders, and simply see the trend as evidence of the need for substantial corporate tax reform so that the United States can become more globally competitive as a home for businesses. However, those with opposing viewpoints may be closer together than they realize, and meaningful reform may be attainable if productive dialogue can be facilitated. This Note provides an overview of trends in corporate taxation, the thirty-year history of inversions and governmental attempts to contain them, and an analysis of recent anti-inversion regulations proposed by Treasury in September 2014. Finally, this Note critiques the legislative and regulatory framework that attempts to restrict the practice of inversions, and provides a suggestion for constructively responding to the trend. Given the passion and diversity of viewpoints on the issue, arriving at a national consensus on how to respond to the recent proliferation of inversions presents an extraordinary challenge. There may, however, be enough common ground for lawmakers to craft a solution that removes the incentive for corporations to invert, thereby shoring up the tax base and making the US economy more competitive globally. In light of the substantial—and rapidly growing—national debt, there is no better time to critically reevaluate the policies and priorities of corporate taxation.
Keywords: Tax Law; Corporate tax inversion; Corporate tax; Corporate taxation; Inversions